2006
DOI: 10.1109/tuffc.2006.188
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of noncontact intracardiac ultrasound ablation and imaging catheter for treatment of atrial fibrillation

Abstract: Atrial fibrillation (AF) affects 1% of the population and results in a cost of $2.8 billion from hospitalizations alone. Treatments that electrically isolate portions of the atria are clinically effective in curing AF. However, such minimally invasive catheter treatments face difficulties in mechanically positioning the catheter tip and visualizing the anatomy of the region. We propose a noncontact, intracardiac transducer that can ablate tissue and provide rudimentary imaging to guide therapy. Our design cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
4
0
2
Order By: Relevance
“…The available literature indicates the possibility of using ultrasound for nonpharmacological treatment of heart failure [1], defibrillation [2], pacing [3], cardiac gene therapy [4], and ablation for treating arrhythmias [5]. …”
Section: Introductionmentioning
confidence: 99%
“…The available literature indicates the possibility of using ultrasound for nonpharmacological treatment of heart failure [1], defibrillation [2], pacing [3], cardiac gene therapy [4], and ablation for treating arrhythmias [5]. …”
Section: Introductionmentioning
confidence: 99%
“…In 2004, the use of a highly integrated multifunctional catheter was described [24] as a 14F device with a 2-D matrix array of 112 elements for 5-MHz imaging surrounded by an ablation annulus operating at 10 MHz, and EP sensors near the catheter tip. Recently, a new 7F catheter integration effort was reported to guide EP interventions with a dual-purpose side-looking 128-element imaging and therapy array operating at 10 MHz [25], which is designed to image as well as ablate tissue around the ostia of left atrium (LA) pulmonary veins.…”
Section: A Conventional Interventional Ep Guidance and Early Ice Devmentioning
confidence: 99%
“…Ultrasound imaging studies [14,15] showed promising results in monitoring RF ablation lesions in animal models but the small field of view of the imaging catheters that were used limits the assessment of the lesion as a whole. In addition, the image features characterizing ablation lesions were neither consistent between studies [16] nor persistent in ex-vivo evaluation setups [17]; a necessary feature for post-ablation lesion continuity assessment. Optical methods, such as near infrared spectroscopy (NIRS), or polarization sensitive-/ optical coherence tomography (PS-/OCT), were also considered for the problem of lesion monitoring [[18], [19], [20], [21]].…”
Section: Introductionmentioning
confidence: 99%